Immunoassay for pyruvate kinase M1/2 as an Alzheimer’s biomarker in CSF - de Geus Matthijs B.; Kivisäkk Pia; Trombetta Bianca A.; Tijms Betty M.; Visser Pieter Jelle; Arnold Steven E.; Carlyle Becky C. (Open Life Sciences)
Alzheimer’s disease (AD) is characterized by amyloid-beta plaques and tau tangles in the brain, but these markers alone do not predict disease progression. The intersection of these pathologies with other processes including metabolic changes may contribute to disease progression. Brain glucose metabolism changes are among the earliest detectable events in AD. Pyruvate kinase (PKM) has been implicated as a potential biomarker to track these metabolic changes. We have developed an enzyme-linked immunosorbent assay (ELISA) to assess PKM levels in cerebrospinal fluid (CSF). First, we verified the relationship of CSF PKM levels with cognitive decline, revealing a correlation between elevated CSF PKM levels and accelerated cognitive decline in preclinical AD patients in a tau-dependent manner. We developed the ELISA using two PKM-specific antibodies and validated it through quality control steps, indicating robust quantification of PKM. We showed that ELISA measurements of PKM correlate with mass spectrometry values in matching samples. When tested on an independent cohort, the assay confirmed elevation of PKM in AD. These findings support the use of PKM as a potential biomarker for tracking early metabolic changes in AD, offering a novel tool for investigating metabolic alterations and their intersection with other underlying pathologies in AD progression.